Barriers of adapting detergent refill shop business model towards sustainable product consumption in Tacloban City - Abendan, Jamaica R.; Flores, Paul D.; Morata, Keisa F.; Piangco, Mark Lester; Sevilla, Ma. Angela G.
Tacloban City produces an average of 113 tons of trash every day with 65% classified as biodegradable and 22% residual waste. Ideally, only the residual waste should be directed to sanitary landfills. In response to environmental concerns, the City Ordinance No. 2023-15-06 was enacted which bans the use of plastic bags and styrofoam as secondary packaging materials in business establishments such as grocery stores, fast food outlets, market vendors, food kiosks, small community stores, and ambulant vendors. However, the use of sachet and single-use plastic is still prevalent in the city Using a mixed-method approach, the research explored the perspectives of three key stakeholders: consumers, business merchandise owners and policymakers. Quantitative findings revealed that consumers show a promising willingness to adapt refill systems, however, there are challenges in economic, accessibility as well as convenience. Meanwhile, qualitative findings from business owners emphasized operational challenges, concerns on profitability and market readiness as challenges to economic viability. On the other hand, policymakers have displayed their lack of proactivity in implementing environmental policies, bureaucratic concerns, financial constraints and reliance on political will. These overarching barriers led to the development of a new and refined detergent refill shop business model designed to promote sustainable product consumption, enhance profitability for business, and support broader environmental goals. This innovative approach provides a practical solution for promoting circular economy practices not only within Tacloban City but across the entire country.